2002
DOI: 10.1007/s00403-002-0292-4
|View full text |Cite
|
Sign up to set email alerts
|

Increase in serum IgE levels following injection of syngeneic keratinocyte extracts in BALB/c mice

Abstract: Increased serum IgE levels are found in atopic diseases, especially atopic dermatitis. It is generally accepted that the high serum IgE levels are increased by exposure to exogenous antigens. However, exposure to antigens in the absence of proper adjuvants does not usually increase serum IgE. Here, we studied the involvement of skin factor(s) in increasing serum IgE. The soluble fractions were obtained from two keratinocyte cell lines, PAM 212 and KCMH-1, derived from BALB/c and CBA/J mice, respectively. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…After 14-weeks feeding of either control or PKGM diet, there was no difference in the appearance and body weight among the groups (30.2 AE 0.5 g for PBS-injected mice fed with control diet, 29.5 AE 0.4 g for PBS-injected mice fed with PKGM diet, 30.7 AE 0.3 g for PAM extractinjected mice fed with control diet, 30.0 AE 0.3 g for PAMextract-injected mice fed with KGM diet). In accordance with our previous report [17], continual injection of PAM extract induced the increase of plasma IgG and IgE levels during the period of the experiment in mice fed with control diet. The levels of plasma IgG and IgE in mice fed with PKGM were significantly lower than those in mice fed with control diet: IgG at 5 and 11 weeks ( Fig.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…After 14-weeks feeding of either control or PKGM diet, there was no difference in the appearance and body weight among the groups (30.2 AE 0.5 g for PBS-injected mice fed with control diet, 29.5 AE 0.4 g for PBS-injected mice fed with PKGM diet, 30.7 AE 0.3 g for PAM extractinjected mice fed with control diet, 30.0 AE 0.3 g for PAMextract-injected mice fed with KGM diet). In accordance with our previous report [17], continual injection of PAM extract induced the increase of plasma IgG and IgE levels during the period of the experiment in mice fed with control diet. The levels of plasma IgG and IgE in mice fed with PKGM were significantly lower than those in mice fed with control diet: IgG at 5 and 11 weeks ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…In general, Th2 cells drive B cells to differentiate and produce Igs by secretion of cytokines such as IL-4 and IL-13. In addition, our previous study has shown that the injections of PAM extract consistently increased the levels of serum IgE, IgG1 and IgG2b [17], suggesting the enhancement of Th2 cellular responses. Thus, the results of this study suggested that PKGM suppresses Th2 cellular responses.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Based on these findings, we hypothesized that skin damage, especially destruction of the epidermis, raises serum IgE. We previously revealed that serum IgE level of BALB/c mouse increased when injected with syngeneic keratinocyte extract, and that this phenomenon was not clearly observed in CBA/j mouse [19], suggesting the close association of genetic background with the effect of keratinocyte extract. It is well known that B-cells produce IgE protein via immunoglobulin class-switching triggered by epsilon germ-line transcription under the influence of both interleukin (IL)-4 and CD40L-CD40 interaction [9].…”
Section: Introductionmentioning
confidence: 99%